Effect of watering frequencies and rehydration on water intake and drinking behaviour of indigenous sheep (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted with the objective to study the effect of watering frequencies and  rehydration on water intake and drinking behaviour pattern of indigenous sheep under intensive production  system during hot humid season. Eighteen adult dry non pregnant farm born Patanwadi and Marwari female  (25-35 kg) sheep were divided randomly on body weight basis in three treatment groups viz., T1: Control  (watering thrice in a day), T2: (12 hrs. watering interval - watering twice in a day), T3: (24 hrs. watering  interval - watering once in a day).The water intake (ml/d, ml/100 kg BW, ml/kg W0.75 and ml/kg DMI) and  total water intake time (sec.) of experimental animals were significantly (P < 0.05) influenced by different  watering frequencies. Moreover, rehydration influenced significantly (P < 0.05) the water intake (ml/d, ml/100  kg BW, ml/kg W0.75 and ml/kg DMI) and drinking behaviour in terms of total water intake time (sec.) and  water intake (ml/sec.) of sheep. The results indicated that the adult sheep should be given ad libitum water  at least thrice a day to maximize water intake (ml/d, ml/100 kg BW and ml/kg W0.75) in hot humid season.
Keywords: Drinking behaviour; Watering frequencies; Water intake